Ion mobility conformational lipid atlas for high confidence lipidomics - Leaptrot, Katrina L.; May, Jody C.; Dodds, James N.; McLean, John A. (Nature communications, 2019)
Lipids are highly structurally diverse molecules involved in a wide variety of biological processes. Here, we use high precision ion mobility-mass spectrometry to compile a structural database of 456 mass-resolved collision cross sections (CCS) of sphingolipid and glycerophospholipid species. Our CCS database comprises sphingomyelin, cerebroside, ceramide, phosphatidylethanolamine, phosphatidylcholine, phosphatidylserine, and phosphatidic acid classes. Primary differences observed are between lipid categories, with sphingolipids exhibiting 2–6% larger CCSs than glycerophospholipids of similar mass, likely a result of the sphingosine backbone’s restriction of the sn1 tail length, limiting gas-phase packing efficiency. Acyl tail length and degree of unsaturation are found to be the primary structural descriptors determining CCS magnitude, with degree of unsaturation being four times as influential per mass unit. The empirical CCS values and previously unmapped quantitative structural trends detailed in this work are expected to facilitate prediction of CCS in broadscale lipidomics research. The biological functions of lipids critically depend on their highly diverse molecular structures. Here, the authors determine the mass-resolved collision cross sections of 456 sphingolipid and glycerophospholipid species, providing a reference for future structural lipidomics studies.